Mutagenic compounds generated from the chlorination of disperse azo-dyes and their presence in drinking water - Oliveira, Danielle P.; Carneiro, Patricia A.; Rech, Celia M.; Zanoni, Maria Valnice Boldrin [UNESP]; Claxton, Larry D.; Umbuzeiro, Gisela A. (Amer Chemical Soc, 2006)
The water produced by the Cristais River Drinking Water Treatment Plant (CR-DWTP) repeatedly produced mutagenic responses that could not be explained by the presence of disinfection byproducts (DBPs) generated by the reaction of humic acids and chlorine. In order to determine the possible role of chlorinated dye products in this mutagenic activity, solutions of a black dye commercial product (BDCP) composed of C. I. Disperse Blue 373, C. I. Disperse Orange 37, C. I. Disperse Violet 93, and chemically reduced BDCP (R-BDCP) were chlorinated in a manner similar to that used by the CR-DWTP. The resulting solutions were extracted with XAD-4 along with one drinking water sample collected from the CR-DWTP. All extracts showed mutagenic activity in the Salmonella/microsome assay. Dye components of the BDCP as well as its reduced chlorinated (Cl-R-BDCP) derivative were detected in the drinking water sample by analysis with a high performance liquid chromatography/diode array detector (HPLC/DAD). The mutagenicity results of these products suggest that they are, at least in part, accounting for the mutagenic activity detected in the drinking water samples from the Cristais River. The data obtained in this study have environmental and health implications because the chlorination of the BDCP and the R-BDCP leads to the formation of mutagenic compounds (Cl-BDCP and Cl-R-BDCP), which are potentially important disinfection byproducts that can contaminate the drinking water as well as the environment.